The search for the genuine : nonfiction, 1970-2015 - Harrison, Jim, 1937-2016 (Grove Press, 2022)
"New York Times-bestselling author Jim Harrison (1937-2016) was a writer with a poet's economy of style and a trencherman's appetites. Best known for fiction and poetry, Harrison was also a prolific nonfiction writer, with columns running in Sports Illustrated and Esquire, and work in Outside, Field & Stream, and others. Written with Harrison's trademark ribald humor, compassion, and full-throated zest for life, The Search for the Genuine is a collection of pieces-from the near-classic to the never-published-that muse on everything from grouse hunting and ocean fishing to Zen Buddhism and matters of the spirit, as well as reporting on Yellowstone and shark-tagging in the open Atlantic, commentary on writers from Bukowski to Neruda to Peter Matthiessen, and a heartbreaking essay on life-and, for those attempting to cross in the ever-more-dangerous gaps, death-on the US-Mexico border. Written with Harrison's trademark humor, compassion, and full-throated zest for life, this chronicle of a modern bon vivant is a feast for fans who may think they know Harrison's nonfiction, from a true "American original" (San Francisco Chronicle)"--